Investigation of the effect of hawthorn after thermal processing on functional dyspepsia based on fecal metabolomics and gut microbiota - Zhang, Lilin; Tian, Yao; Liang, Qi; Wu, Chunjie; AI, Li (Food Science and Technology, 2023)
Hawthorn is an important medicine food homology (MFH) species. Charred hawthorn (CH) is derived from the thermal processing of raw hawthorn (RH). Traditional Chinese medicine theory suggests that CH has a stronger effect to promote digestion than RH. In this study, based on the functional dyspepsia (FD) model in rats, the effects of RH and CH on gastrointestinal motility were investigated, and the mechanism of action was revealed from the perspectives of gut microbiota and metabolomics. FD model was established by various stimulation and chronic induction methods for 21 days. After 7 days of intervention, CH could improve the gastric emptying rate and intestinal propulsion rate; correct the abnormal levels of 20 different metabolites in the feces; regulate the metabolic pathways of vitamin A and niacin; increase the diversity and richness of intestinal microbiota and adjust the structure and composition of gut microbiota in FD rats. And the effect of CH is better than RH. The results of this study show that CH can better modulate the metabolites and gut microbiota of rats with FD, to provide a theoretical basis for the development of dietary therapy of hawthorn as a treatment plan or adjuvant treatment for FD.